Jonas Hanway's scurrilous, scandalous, shockingly sensational umbrella - Crute, Josh (Page Street Kids, 2020)
Sometimes in London it drizzles. Sometimes it mizzles. Other times it pelts and showers and spits. And Jonas Hanway hates getting wet. How can he go about his day as a proper London gentleman when his shoes are soggy, his coat is always collecting puddles, and his wig looks like a wet cat? Fed up with damp and dreary London, Jonas sails far away, to places where the sun always shines. But what he sees when he gets there is ... scandalous! Shocking! Sensational! Perhaps also ... quite genius? Now all Jonas has to do is convince the rest of London that they need an umbrella, too. All about the real gentleman who introduced umbrellas to 1750's London society, this is the perfect story of persistence, problem-solving, and how good ideas hold (off) water.